The influence of leader humor on employee creativity: from the perspective of employee voice - Cao, Yi; Zhou, Keqiucheng; Wang, Yijiang; Hou, Yubo; Miao, Rentao (Frontiers in Psychology, 2023)
Creativity is the primary factor generating transformation. This study explored the impact of leader humor on employee creativity (incremental and radical creativity) from the perspective of employee voice. Data were collected from 812 Chinese employees through multipoint surveys. The results found that (1) leader humor has a significant positive effect on employee incremental and radical creativity; (2) promotive/prohibitive voice mediates the relationship between leader humor and employee incremental/radical creativity separately; (3) contradiction thinking moderates the effect of leader humor on prohibitive voice and further moderates the indirect effect of leader humor on radical creativity; and (4) the moderated mediation model mainly applies to state-owned enterprises rather than private-owned enterprises. The theoretical and practical implications of these findings are discussed.